Effect of different sized CeO2 nano particles on decomposition and hydrogen absorption kinetics of magnesium hydride - Singh R.K.; Sadhasivam T.; Sheeja G.I.; Singh P.; Srivastava O.N. (My University, 2025)
In present paper, different sizes of CeO2 nanoparticles were synthesized by ball milling and their effect on the absorption kinetics and decomposition temperature of MgH2 was studied. It was found that a small amount of admixing of the above said catalysts with MgH2 exhibits improved hydrogen storage properties. Among these different sizes of CeO2 nanoparticles, 2 weight % admixed CeO2 with a particle size of ∼10-15 nm led to decrease in desorption temperature by ∼50 K. Moreover, it also shows 1.5 times better absorption kinetics with respect to pure MgH2. The samples were characterized using SEM, TEM and XRD techniques. The hydrogenation/dehydrogenation properties were measured by gas reaction controller. Copyright © 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.